KETAATAN DALAM MENGAWALI PELAYANAN KAJIAN MATIUS 4:1-11 - Imelda Ch Pocerattu (IAKN Ambon, 2020)
The world is a place for the church to carry out its ministry. Along with that, the world will continue to experience changes and developments in all aspects of life. The various problems that occur in this world also affect the existence of the church, both positive and negative. The trials of Jesus that Jesus experienced in the wilderness explain several things, namely: The trials in the wilderness have shown that as the Son of God, Jesus showed His obedience to the Father, in fulfilling the Messianic work He would do. Second, Jesus is the Son of God who came to fulfill the prophecy in the PL. The evangelist Matthew wanted to emphasize that Jesus was greater than Adam and Moses, as well as the nation of Israel. If Adam, Moses, and the Israelites failed to show obedience to God in the face of temptation, then Jesus showed His obedience to God, so He overcame the temptation of the devil. Third, Jesus defeated the devil, and Jesus' victory became the way for Him to deliver those who were oppressed and taken captive by the devil. The only purpose of the devil is to make people submit and worship him. The temptations offered by the devil to Jesus are often experienced by believers today. These materials are, economics (Matt. 4: 2-3), Position (Matt. 4: 5-7), Power (Matt. 4: 8-10). Learning from Jesus' attitude in the face of trials, Christians must be critical of the problems that arise, and always lean on God.